RETRACTED: An Analytical Study on the Political and Intellectual Legacies of Necmettin Erbakan and Atilla İlhan - Ali @ Mat Zin, Aizan (Journal of Al-Tamaddun, 2025)
This study analyses the political and intellectual legacies of Necmettin Erbakan and Atilla İlhan, two influential figures in modern Turkish history whose ideologies have significantly shaped Türkiye’s political landscape. The main research question guiding this study is: How did the political and intellectual contributions of Erbakan and İlhan influence the development of Türkiye’s nation? The data collection method involved a documentation of primary sources, including speeches, political writings, and literary works of both figures. This was supplemented by secondary sources analysing their influence in Turkish political and intellectual circles. The analysis employed a thematic and comparative approach. The findings reveal that while Erbakan’s legacy has contributed to the rise of the AKP and political Islam, İlhan’s intellectual work has provided a strong secular and anti-Western critique that has influenced Türkiye’s intellectual left and ongoing debates about Türkiye’s place in the West. Despite their contrasting ideologies, both figures significantly contributed to the shaping of Türkiye’s national identity and its complex relationship with secularism and Islamism. The study suggests that contemporary political movements in Türkiye, particularly those related to Islamist policies and secular-nationalist discourse, are deeply informed by the legacies of both Erbakan and İlhan. In conclusion, the paper underscores the continuing relevance of their ideas in understanding the dynamics of Türkiye’s political identity, offering insights for future research into the influence of political ideologies on Türkiye’s evolving relationship with its past and future trajectory in the globalized world.